Are Fund Staff Projections of Debt More Optimistic Under Program Contexts?. (Policy Papers; Policy Paper ;, 2005)
This note examines whether projections made in the context of a Fund-supported program are systematically more optimistic than those done for surveillance cases. Of particular interest in this regard is the assessment of external debt sustainability, as this underlies the "capacity to repay the Fund" analysis. Accordingly, this note examines debt projections over the period 1990-2004, with data for transition countries beginning in 1995.